24‐hour monitoring of transient lower esophageal sphincter relaxation events by long‐term high‐resolution impedance manometry in normal volunteers: The "mirror phenomenon". Issue 3 (24th January 2019) - He, Suyu; Jell, Alissa; Hüser, Norbert; Kohn, Nils; Feussner, Hubertus
Abstract: Background: The aim of this study was to investigate the frequency and circadian changes in transient lower esophageal sphincter relaxations (TLESRs) in normal volunteers using 24‐hour high‐resolution impedance manometry (HRIM). Methods: Fifteen volunteers underwent HRIM. TLESRs were recorded during the mealtime, 2‐hour postprandial, daytime, and supine periods. The catheter was firmly secured to the nose, and subjects went home, ate normal meals, and continued routine daily activities. Key Results: Successful recordings were obtained in 11 volunteers. Overall, 1083 TLESRs were documented; the average occurrence was 4.2/h, and the duration was 21.0 ± 5.2 seconds. The majority of the TLESRs occurred during the 2‐hour postprandial (42.7%) and daytime (31.5%) periods, while 10.2% and 15.6% occurred during the mealtime and supine periods, respectively. Eight hundred and eighty‐six (81.8%) TLESRs were associated with reflux. Overall, 25.5% of TLESRs were preceded by partial secondary peristalsis (PSP), while 74.5% were preceded by nothing. Terminating events included primary peristalsis (PP; 40.3%), PSP (42.8%), full secondary peristalsis (FSP; 8.2%), or nothing (8.7%). Both preceding and terminating events periodically changed throughout the four periods. One hundred and twelve (10.3%) TLESRs with both preceding and terminating events of PSP, presenting as a "mirror phenomenon, " were documented. The majority of these TLESRs occurred during the supine (70.5%). Conclusions & Inferences: Transient lower esophageal sphincter relaxations are common physiological motor events in normal volunteers; these events have certain circadian rhythms, as do the events that precede and terminate TLESR events. A special "mirror phenomenon" is observed when both the preceding and terminating events are PSP. Abstract : Transient lower esophageal sphincter relaxations are a normal physiological motor event. It has certain circadian rhythms; a special "mirror phenomenon" is presented when both the preceding and terminating events are partial secondary peristalsis (PSP).